2018
DOI: 10.31014/aior.1992.01.02.12
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Effect on Trust on Customer Satisfaction and Customer Loyalty Relationship in Malaysian Airline Industry

Abstract: This research aims to find out the main factors that affect customer loyalty in the airline industry in Malaysia because customer loyalty is regarded as the ultimate goal for the marketing behavior (Heskett, 2002;McMullan & Gilmore, 2008). Gaining customer loyalty and maintaining brand loyalty with customers is critical for the company to survive in a competitive environment (Heskett, 2002). It would contribute and assist airline industry in developing future strategies on how to enhance customer loyalty. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…In some studies, trust has been described as the antecedent of customer loyalty, but not quite its main antecedent, but other mediators or moderators are required. Trust has no attachment or social relational role for it to generate customer loyalty, whereby the role of social attachment and interactive communication between a seller and buyer will bridge the establishment of customer loyalty (Doney & Cannon, 1997;Kaur & Soch, 2018;Lin et al, 2018;Ponder et al, 2016;Sirdeshmukh et al, 2002;Tabrani et al, 2018;Veloutsou, 2015). Without intimacy between a seller and buyer, the development of trust will have limited advantages and may not yield long-term relations (customer loyalty).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, trust has been described as the antecedent of customer loyalty, but not quite its main antecedent, but other mediators or moderators are required. Trust has no attachment or social relational role for it to generate customer loyalty, whereby the role of social attachment and interactive communication between a seller and buyer will bridge the establishment of customer loyalty (Doney & Cannon, 1997;Kaur & Soch, 2018;Lin et al, 2018;Ponder et al, 2016;Sirdeshmukh et al, 2002;Tabrani et al, 2018;Veloutsou, 2015). Without intimacy between a seller and buyer, the development of trust will have limited advantages and may not yield long-term relations (customer loyalty).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, customer sentiment, as a significant emotional attitude, plays a crucial role in shaping customer loyalty and encouraging repeat business within the airline industry. Recent studies strongly support this notion, providing evidence of the intricate relationship involved (Lin et al, 2018). For example, Lin et al (2018) examined the Malaysian airline industry and found that trust acts as a positive and influential factor that mediates the link between customer satisfaction and customer loyalty.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Hasil ini sesuai dengan penelitian yang dilakukan (Wulur et al, 2020), (Chou et al, 2019), (Lin et al, 2018), (Fadhilah, Cahyani, et al, 2022) kepercayaan berpengaruh positif dan signifikan terhadap kepuasan konsumen. Hal ini membuktikan bahwa semakin tinggi tingkat kepercayaan maka semakin tinggi kepuasan konsumen.…”
Section: Nilai Terendahunclassified